Pin-on-Disc Experimental Study of Thermomechanical Processes Related to Squeal Occurrence - Quentin Caradec; Sacha Durain; Maël Thévenot; Mathis Briatte; Merten Stender; Jean-François Brunel; Philippe Dufrénoy (Lubricants)
Squeal refers to a sustained high-intensity noise resulting from friction-induced vibrations. Although it is known that it originates from mode coupling, the conditions under which it occurs are still unclear, especially regarding the contact conditions. In this paper, pin-on-disc experimental tests are conducted in order to investigate the conditions of squeal occurrence. The tests are highly instrumented: they involve in particular a detailed measurement of near-surface temperature evolution in the pin using 16 thermocouples and a discrete monitoring of the evolution of surface profiles. As expected, the squealing frequency is closely related to the temperature level. However, the mean temperature level alone is not sufficient to predict the occurrence of squeal, especially at low temperatures. The study of local temperature elevations over the pin surface coupled with surface observations allows for assessing the evolution of macroscopic contact localization during tests at low temperatures. The contact localization is shown to be related to squeal episodes: at low temperatures, the contact is localized near the corners of the pin surface, and squeal is found to occur only in situations where the contact is evenly balanced over the corners, which is highly influenced by the initial pin surface profile. This shows that the conditions of squeal occurrence are driven in a significant extent by thermomechanical processes.